PROBLEMATIKA PENEGAKAN HUKUM TERHADAP TINDAK PIDANA POLITIK UANG DALAM PEMILIHAN UMUM DI INDONESIA - Kania, Dede (Bawaslu Provinsi Jawa Barat, 2023)
Money politics is one of the offenses regulated in election crimes. Whatever the amount and whatever form, money politics remains dangerous because it has an impact on the quality of democracy. The determination of money politics as a form of criminal act shows the desire of legislators to prevent money politics in elections. In fact, money politics is increasingly common and is even considered inseparable from elections. The specifications of this research are descriptive-analytical, to describe the phenomena and legal facts of money politics that occurred in the Indonesian elections. The research approach uses normative juridical. The results of the research show that law enforcement against criminal acts of money politics has not been effective. Problems in law enforcement are found in 3 (three) things, namely legal substance which is limited to the target perpetrator, understanding and consistency of law enforcement officials at election law enforcement centers in handling money crimes, as well as guaranteeing political education and public legal awareness.